Cardiopulmonary disease as sequelae of long-term COVID-19: Current perspectives and challenges - Oliveira, Rudolf K. F.; Nyasulu, Peter S.; Iqbal, Adeel Ahmed; Hamdan Gul, Muhammad; Ferreira, Eloara V. M.; Leclair, John William; Htun, Zin Mar; Howard, Luke S.; Mocumbi, Ana O.; Bryant, Andrew J.; Tamuzi, Jacques L.; Avdeev, Sergey; et al. (Frontiers in Medicine, 2022)
COVID-19 infection primarily targets the lungs, which in severe cases progresses to cytokine storm, acute respiratory distress syndrome, multiorgan dysfunction, and shock. Survivors are now presenting evidence of cardiopulmonary sequelae such as persistent right ventricular dysfunction, chronic thrombosis, lung fibrosis, and pulmonary hypertension. This review will summarize the current knowledge on long-term cardiopulmonary sequelae of COVID-19 and provide a framework for approaching the diagnosis and management of these entities. We will also identify research priorities to address areas of uncertainty and improve the quality of care provided to these patients.